The impacts of endothelial cell senescence on ageing-related blood-brain barrier dysfunction and the potential therapeutic strategies - Ya, Jingyuan (2025)
Background: Disruption of the blood-brain barrier (BBB) contributes to various agerelated neurological disorders. Brain microvascular endothelial cells (BMECs) are the most critical components of the BBB, forming a tightly sealed yet selectively permeable monolayer to maintain central nervous system (CNS) homeostasis. The accumulation of senescent cells in the CNS is thought to play a significant role in age related BBB dysfunction. A large number of recent pre-clinical and clinical studies have focused on the development of senotherapeutic interventions to prevent or delay BBB ageing and extend health span. However, the understanding of BMEC senescence and age-related BBB dysfunction remains limited, and studies illustrating the effects of potential interventions are urgently needed.